2014
DOI: 10.1088/1751-8113/47/8/085303
|View full text |Cite
|
Sign up to set email alerts
|

Perturbing free motions on hyperspheres without degeneracy lift

Abstract: We consider quantum motion on S 3 perturbed by the trigonometric Scarf potential (Scarf I) with one internal quantized dimensionless parameter, ℓ, the ordinary orbital angular momentum value, and another, continuous parameter, b, through which an external scale is introduced. We argue that a loss of the geometric hyper-spherical so(4) symmetry of the free motion occurs that leaves intact the unperturbed hydrogen-like degeneracy patterns characterizing the spectrum under discussion. The argument is based on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…To be specific, we are interested in the possibility to formulate effective (one-color) chromo-statics on S 3 . In parallel to electrostatics, one may start approaching this goal by considering the fundamental solutions to the S 3 Laplace operator in (17). It is not difficult to cross check that the (− q 4π tan χ) function, where q stands for a color charge, is such a solution, ∆ S 3 (χ, θ, ϕ) tan χ = 0.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To be specific, we are interested in the possibility to formulate effective (one-color) chromo-statics on S 3 . In parallel to electrostatics, one may start approaching this goal by considering the fundamental solutions to the S 3 Laplace operator in (17). It is not difficult to cross check that the (− q 4π tan χ) function, where q stands for a color charge, is such a solution, ∆ S 3 (χ, θ, ϕ) tan χ = 0.…”
Section: Discussionmentioning
confidence: 99%
“…If the B(R) parameter were to be in some way related to the dilaton mass, then the latter could throughout leave the conformal symmetry intact. In more technical terms, it can be shown that the Hamiltonian in (65) is intertwined with the χ dependent part of the Lapalcian in (17). The parameter values fitting the data are listed in the Table 1.…”
Section: Data Fit By the (Sec 2 χ +Tanχ) Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to get an insight into the symmetry properties of the perturbed Hamiltonian for this case one has to follow the standard procedure and find the complete set of operators with which it is commuting. In calculating the commutators of these operators, a clue on a possible Lie algebra might be obtained [19].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, such equations can also be handled by the so called factorization method underlying modern super-symmetric quantum mechanics (see [7] for details), or by employing the recently elaborated Nikiforov-Uvarov method [15]. The solutions to (19) are given, among others, in [12]. Upon equipping the wave functions with quantum numbers according to,…”
Section: Exotic Degeneracy Preserving Perturbation Of the Rigid Rotatormentioning
confidence: 99%